Cryptogenic colitis due to occult cytomegalovirus infection. Issue 1 (28th September 2010) - Marks, Daniel J B; Smith, Philip J; Rahman, Farooq Z; Miller, Robert F; Ledermann, Jonathan A; Bloom, Stuart L
Abstract : Colitis secondary to cytomegalovirus infection is well recognised and usually straightforward to diagnose. Here two cases are reported in whom all initial investigations failed to demonstrate the presence of virus, with potential adverse consequences for its treatment. A case is made for empirical antiviral therapy despite negative investigations if clinical suspicion is high.